Novel inkjet direct printing technology based on thermosensitive sol–gel transition inks. Issue 23 (December 2022) - Li, Yan; Sun, Xiaoshi; Chang, Guangtao; Li, Ruoxin
Biodegradable poly( ε -caprolactone-co-lactide)- b -poly(ethylene glycol)- b -poly( ε -caprolactone- co -lactide) (PCLA-PEG-PCLA) triblock copolymer was developed to prepare thermosensitive inks for digital fiber printing applications. The thermosensitive inks can be printed on any textile or fiber that does not need to go through the pretreatment and soaping procedure like traditional inks. This copolymer aqueous solution has a reversible sol–gel transition property, which can be used to prepare thermosensitive sol–gel inks. PCLA-PEG-PCLA had little effect on the physical properties of the inks, including the average particle size, conductivity, and surface tension at room temperature. However, the viscosity of the thermosensitive inks can increase dramatically under high temperature. This was due to the inks undergoing a sol–gel transition with an increase of temperature. The inks were in the sol state in the printer cartridge at room temperature and when the ink drops fell on the heated fiber or textile, a sol–gel transition occurred and turned them into a gel immediately. The high viscosity prevented the ink from spreading around on the fabrics, thus giving a sharp edge. The study indicated that the line width printed by thermosensitive inks was reduced to 266.35 μm from 464.08 μm in the weft direction (reduced by 43%), and the line width in the warp direction was reduced to 264.35 μm from 385.76 μm (reduced by 32%). The polyester fabric printed by thermosensitive ink has a higher color strength ( K / S ) at 47–50°C with excellent colorfastness. Thermosensitive ink is a type of innovative ink, in line with the concept of green ecological textile manufacturing.